COMPARATIVE ANALYSIS OF ALTMAN, SPRINGATE AND ZMIJEWSKI MODELS IN PREDICTING BANKRUPTCY - Anwar Anwar; Reni Restriani Utami (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
This study aims to determine the potential for bankruptcy in timber sub-sector companies and their management that are listed on the Indonesia Stock Exchange for the 2017-2020 period using the Altman, Springate, and Zmijewski models and to find out the comparison of the three models. This type of research is quantitative research. The research population is the company's sub-sector of wood and its processing. The research sample is PT. SLJ Global Tbk (SULI) and PT. Tirta Mahakam Resources Tbk (TIRT). Data analysis techniques use the Altman, Springate, and Zmijewski models. The results of the study show that SULI and TIRT are predicted to experience potential bankruptcy in 2017-2021 using the Altman and Zmijewski model. 2018-2021 for SULI and 2020-2021 for TIRT using the Springate model. The results of the Mann Whitney test show that there is no difference in predicting the potential for bankruptcy of SULI and TIRT using the three models.